Pengaruh Kualitas Layanan Terhadap Kepuasan Dan Dampakanya Terhadap Kepercayaan Serta Loyalitas - Cahyani, Komang Indah Gita; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
Government through PT. Jasa Raharja (Persero) provides benefit to society of the unfortunate accident on the way, which is guaranteed in accordance with Law no.33/1964 jo PP No.17/1965 and Law. 34/1965 jo PP No.18/1965. Implementation of compensation, needed some compensation for prior service procedures. For that very overlooked good quality service from Jasa Raharja to people who want to receive compensation. So that what the customer expectations can be realized according to their expectations. This study was conducted to determine the effect of service quality on satisfaction, and their impact on trust and customer loyalty Jasa Raharja Cabang Bali. This research was conducted in the area of Bali. The sample size of 100 people were taken by random sampling method. Data was collected through questionnaires that use numerical scale of 5 points to measure 28 indicators. The analysis technique used is regression analysis with the approach path. Suggestion for the company, to improve the quality of service is very important to consider variables such as satisfaction, trust and loyalty. The three variables are highly related in maintaining a good level of quality companies, so companies have been consistently providing the best service for community. Keywords: Quality of Service, Satisfaction, Trust, Loyalty
Keywords: Quality of Service, Satisfaction, Trust, Loyalty